Cyclic voltammetry and charge/discharge cycles of conductive polymer on screen-printed carbon and platinum electrodes in aqueous media - Wan Salim, Wan Wardatul Amani; Benoudjit, Abdel Mohsen; Ihda Uswah Solehah, Shohibuddin; Tumian, Afidalina (2019)
Electropolymerized conductive polymer (PEDOT:PSS) onto screen-printed carbon electrodes (SPCEs) and screen-printed platinum electrodes (SPPEs) were studied for anodic/cathodic peak current and charge/discharge stability. Cyclic voltammetry (CV) for PEDOT:PSS/SPCEs and PEDOT:PSS/SPPEs in potassium ferricyanide K3[Fe(CN)₆] was conducted to determine redox ability and adhesion of PEDOT:PSS to the carbon and platinum working electrode surface. Furthermore, charge/discharge cycle was performed on the electrodes in phosphate buffer solution at pH 7.1 for 1500 cycles and 10 cycles each day for 15 days to test the stability. From CVs the redox ability of PEDOT:PSS/SPCEs was significantly improved from the unmodified SPCEs in comparison to PEDOT:PSS/SPPEs; the peak current difference of oxidation and reduction (ΔI) for PEDOT:PSS/SPCEs was ~3 times higher than PEDOT:PSS/SPPEs (ΔISPCE = 350 μA, ΔISPPE = 125 μA). For the adhesion of PEDOT:PSS to SPCE and SPPE working electrode surface, the oxidation and reduction peak current of the CVs showed to be almost stable for over 15 days. The results suggest that the electropolymerized PEDOT:PSS had a good adhesion to SPCEs and SPPEs surface. Furthermore, there was insignificant change in the charge/discharge curve after 1500 cycles compare to the initial cycle (p-value = 0.5). In addition, there was insignificant change in the charge/discharge curve after 15 days in comparison to the first day (p-value = 0.9). The results imply that PEDOT:PSS/SPCE transducer maintained its electrochemical stability similar to PEDOT:PSS/SPPE. In conclusion, electropolymerized PEDOT:PSS onto carbon and platinum electrodes can be used for sensors and energy storage applications, where a sufficiently high peak current and stable charge/discharge is required especially in aqueous media.